Effects of single and repeated infections with Neoparamoeba perurans on antibody levels and immune gene expression in Atlantic salmon (Salmo salar). Issue 2 (February 2015) - Valdenegro-Vega, Victoria A.; Polinski, Mark; Bridle, Andrew; Crosbie, Philip; Leef, Melanie; Nowak, Barbara F.
Abstract Amoebic gill disease (AGD) is the main health problem for the salmon industry in Tasmania, Australia and is now reported in most salmon producing countries. Antibody and gene expression responses to the pathogen, Neoparamoeba perurans, have been studied independently following primary exposure; however, the effects of sequential reinfection, which can often occur during net-pen culture of salmon, remain unclear. The association between the transcription of immunoglobulin (Ig) and their systemic and mucosal antibody levels in regards to AGD is unknown. Herein, we assessed the antibody responses as well as Ig transcription in the gills of Atlantic salmon infected only once and also sequentially with N. perurans. After four successive AGD challenges, no significant differences in plasma or skin mucus levels of IgM were observed between AGD-naïve and challenged fish. However, IgM gene expression in gill lesions of AGD-affected fish increased up to 31 d after infection, while no changes in IgT, TCR and CD8 transcription were observed. Changes at IgM transcription level did not match the lack of antibody response in mucus, which is possibly explained by weak correlations existing between protein and mRNA abundances in cells and tissues. In the second experiment, which investigated Ig responses to AGD at the transcriptional as well as antibody production level in salmon after a single infection, the levels of serum or skin mucus IgM antibody were not affected and no changes in the IgM or IgT transcription were induced.